2019
DOI: 10.1371/journal.pone.0210826
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to care of HIV positive clients in a community based HIV counselling and testing programme: A success story of non-governmental organisations in a South African district

Abstract: IntroductionAlthough current data projects South Africa potentially meeting the UN target to test 90% of all people living with HIV by 2020, linking them to HIV care remains a big challenge. In an effort to increase linkage to care (LTC) of HIV positive clients an innovative collaborative intervention between two non-governmental organisations was developed and implemented between 2016 and 2017. This paper investigated the outcome of this collaborative intervention.MethodsWe used a mixed methods approach to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
5
26
0
1
Order By: Relevance
“…The approach assisted parents/guardians to quickly navigate the ART clinic and obtain care for their children. The excellent linkage rate observed in our study was comparable to those reported for a South African ART program that utilized escort services to facilitate linkage to treatment among HIV positive adults, and scale-up of this approach in the Nigeria HIV program will ensure that identified HIV-positive children are offered ART [25].…”
Section: Plos Onesupporting
confidence: 75%
“…The approach assisted parents/guardians to quickly navigate the ART clinic and obtain care for their children. The excellent linkage rate observed in our study was comparable to those reported for a South African ART program that utilized escort services to facilitate linkage to treatment among HIV positive adults, and scale-up of this approach in the Nigeria HIV program will ensure that identified HIV-positive children are offered ART [25].…”
Section: Plos Onesupporting
confidence: 75%
“…Several other factors contributed and these include relationship management between the CBCT programme and health facilities, provision of client escort services to facilities, addressing barriers at the health facility level including task shifting of administrative duties to non-clinical staff. Some of the successes in linkage to care and treatment in this programme were reported before[37].…”
Section: Discussionmentioning
confidence: 96%
“…In South Africa, contracting with a non-governmental organisation to provide escorted transport from home to referral facility increased ART enrolment from 27% at baseline to 85% post intervention [22]. In Nigeria, the Community Treatment Initiative started PLHIV (who had previously refused ART) on treatment in the community.…”
Section: General Adult Populationsmentioning
confidence: 99%